Foraminifers and stable isotopes (О16/О18 and C12/С13) of their shells at methane seepages on eastern slope of Sakhalin Island (Okhotsk Sea) - Sergey P. Pletnev; Vladimir K. Annin; Yu. . Wu; Tatiana S. Tarasova (Известия ТИНРО)
Benthic foraminifers at methane seepages, independently of their taxa and microhabitat preferences, have lower value of d13С than those found in other sites, that’s why these species potentially could be used as bioindicators of methane emission. Species composition and distribution of Foraminifera is analyzed on the samples collected in the cruise of RV Academic M.A. Lavrentyev on 18 stations located on the eastern slope of Sakhalin Island within the depth range 600-1500 m in June 2010. Concentrations of methane in the bottom water and sediments of the surveyed area were high and sometimes exceeded the maximal permissible level in 100 times and more; methane contaminated the whole water column (600 m) and lowered abundance of zooplankton. Both benthic (75 species) and planktonic foraminifers (6 taxa) are investigated. The benthic foraminifers avoided the methane ejections but preferred to settle in places of its diffusive infiltration where their abundance was high, presumably because of blooming of chemoautotrophic bacteria in bottom sediments saturated by methan. The genera Nonionellina, Valvulineria, Uvigerina and the species Reophax dentaliniformis were the most adapted for the polluted environment. Stable isotopes O16/O18 and C12/C13 are measured in carbonate shells of Uvigerina parvocostata, Valvulineria sadonica, Nonionellina labradorica . Intraspecific changes of d18О were insignificant, it varied in the ranges 3.43-3.60, 2.81-3.04, and 3.28-3.37 ‰, respectively. Variability of d13C was higher - 0.9-2.0 ‰ for U. parvocostata and N. labradorica and its value dropped to -1.54 ‰ for the specimens of V. sadonica in the sites of methane seepage. Thus, V. sadonica is the best species-indicator of methane emission.